2022
DOI: 10.3389/fendo.2022.1043919
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a machine learning-augmented algorithm for diabetes screening in community and primary care settings: A population-based study

Abstract: BackgroundOpportunely screening for diabetes is crucial to reduce its related morbidity, mortality, and socioeconomic burden. Machine learning (ML) has excellent capability to maximize predictive accuracy. We aim to develop ML-augmented models for diabetes screening in community and primary care settings.Methods8425 participants were involved from a population-based study in Hubei, China since 2011. The dataset was split into a development set and a testing set. Seven different ML algorithms were compared to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
2
1
0
Order By: Relevance
“…Our results indicated that the inclusion of laboratory variables in the prediction models significantly improved the performances compared to the models developed exclusively with non-laboratory variables, suggesting the considerable role of laboratory variables in the insulin sensitivity assessment models developed by machine learning. These results seemed consistent with the findings in previous research that the inclusion of laboratory variables such as urinary glucose, urinary vitamin C, and FPG improves the accuracy of diabetes prediction models developed by GBM or LightGBM ( 42 , 45 ). Noteworthy, the laboratory features (e.g., fasting glucose, serum lipids, liver enzymes, etc.)…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results indicated that the inclusion of laboratory variables in the prediction models significantly improved the performances compared to the models developed exclusively with non-laboratory variables, suggesting the considerable role of laboratory variables in the insulin sensitivity assessment models developed by machine learning. These results seemed consistent with the findings in previous research that the inclusion of laboratory variables such as urinary glucose, urinary vitamin C, and FPG improves the accuracy of diabetes prediction models developed by GBM or LightGBM ( 42 , 45 ). Noteworthy, the laboratory features (e.g., fasting glucose, serum lipids, liver enzymes, etc.)…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, our results showed that the streamlined LightGBM models utilizing the top-20 ranked variables exhibited comparable performances to the models constructed with all features. Likewise, our previous study indicated that the streamlined diabetes prediction model utilizing the top 20 variables developed by the LightGBM algorithm, exhibited great performances similar to that of the model using all variables (45), which is consistent with the findings in the present study. Moreover, it is reported that the simplified model for gestational diabetes prediction using 9 variables based on LightGBM demonstrates only a modest reduction in predictive accuracy compared to its full variable model (38).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Healthcare intrinsically involves significant human interaction, where empathy and active listening are paramount. Implementing AI technologies complements human interaction by mitigating cognitive biases such as unconscious reasoning, gut feelings, and heuristic shortcuts through the application of AI algorithms (7).…”
Section: Introductionmentioning
confidence: 99%